The Spirituality of the Law in Early Modern Lutheranism - Astorri, Paolo (Studies in spirituality, 2019)
"The law is spiritual", says Paul in Romans 7:14. Martin Luther, Philip Melanchthon, Martin Chemnitz and Johann Gerhard used this passage as a core text to defend the idea that the divine and natural law need both faith and the Holy Spirit to be fulfilled. The law demands a love from the depth of the heart, they argued, but human nature is corrupted by sin and is incapable of loving God. Hence, by the grace of the Holy Spirit alone can man love God and begin a new obedience to His law.